Pengaruh Pengalaman Kerja, Disiplin Kerja, Motivasi Kerja terhadap Prestasi Kerja Pegawai pada Dinas Kebudayaan dan Pariwisata Kabupaten Toraja Utara - Ira Bura; Chrismesi Pagiu; Astriwati Biringkanae (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to determine the influence of work experience, work discipline, work motivation on employee work performance at the North Toraja Regency Culture and Tourism Service. The type of research used is a quantitative deckriptive approach. Sampel zise used in was 28 respondents.The data collection procedure for this research is:observation and questionnraires. This research used multiple linear regression analysis with SPSS 23rd version. The results of this research are partial (t test) showing that the variabel influence work experience, work discpline, and work motivation have no effect on the work performnce on employment on the North Toraja Regency Culture and Tourism Office. Meanwhile, the results of simultaneous research (f test) show that the, work discipline and work motivation have an influence on work performance on the North Toraja Regency Culture and Tourism office.